Transmitting Side Power Control for Dynamic Wireless Charging System of Electric Vehicles - Diep, N. T.; Trung, N. K. (Engineering, Technology & Applied Science Research, 2022)
This paper proposes a new power control method in dynamic wireless charging systems for electric vehicles. A dual-loop controller is proposed to control charging power while the electric vehicle is moving without communication between the transmitting and receiving sides. The output power is estimated through the coupling coefficient estimation. However, the coupling coefficient varies with the position of the vehicle. Therefore, this paper also presents an easy-to-do practical estimation method from the transmitting side, in which the coupling coefficient value is continuously updated according to the vehicle’s position. As a result, the output power is controlled according to the required level with an error of less than 5%.